(untitled) (Revista Electrónica Calidad en la Educación Superior, 2023)
This article describes the implementation of a Virtual Institutional Well-being program at Konrad Lorenz Foundation University in Bogotá, Colombia. This virtual platform consists of virtual learning objects in cultural, sports, and recreational activities, which were designed to contribute to the comprehensive education of the university community. This virtual space has had a significant impact on the participation of the university community, highlighting the importance of providing accessible virtual spaces for the university community. It is expected that the Institutional Well-being department will continue to generate different virtual content based on the interests of the community.